PENGEMBANGAN PERANGKAT ASESMEN AUTENTIK DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN - Abdul Basit; Ludfi Arya Wardana (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2016)
The purpose of writing is to describe the procedure of this development is to produce products such as assessment tools consisting of authentic assessment guidelines, student activity sheet and recapitulation software to teachers for students of Class V semesters I. Eligibility of products based on the level of validity of the experts, the level of implementation and a high reading level through product trials. Data collection instruments used include sheet validation experts, questionnaire responses of students and teacher feedback questionnaire. The findings of the research and development show that the results of the validation test experts expressed very valid with an average score of 4.11. The level of implementation of products with an average score of 4.27. reading level product with an average score of 4